2011
DOI: 10.1590/s1806-83242011005000009
|View full text |Cite
|
Sign up to set email alerts
|

Age estimation of indian adults from orthopantomographs

Abstract: The aim of this study was to develop a method for estimating the chronological age of Indian adults based on the relationship between age and various morphological variables of canine teeth, obtained using orthopantomographs. Orthopantomographs of 120 selected patients were digitized, and radiographic images of the right maxillary canine in each case were processed using a computer aided drafting program. Pulp/ tooth area ratio, pulp/root length ratio, pulp/tooth length ratio, pulp/root width ratio at the ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 8 publications
(18 reference statements)
4
40
0
1
Order By: Relevance
“…Several studies have used orthopantomographs, 14,18,19 but we used periapical radiographs in this study because they produced more reliable data with lower chances of superimposition. 4,18,20,21,22,23,24 One of the difficulties we encountered was achieving the desired sample size because all radiographs did not show 4 healthy canines. This issue was more common in patients aged 60 years and older.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have used orthopantomographs, 14,18,19 but we used periapical radiographs in this study because they produced more reliable data with lower chances of superimposition. 4,18,20,21,22,23,24 One of the difficulties we encountered was achieving the desired sample size because all radiographs did not show 4 healthy canines. This issue was more common in patients aged 60 years and older.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was similar to other studies. 7,19,20,21,22,23,24 Studies that used the method reported here 14,18,22,23,24 showed that sexual dimorphism did not significantly influence age estimation equations; hence, we did not evaluate the sexes separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 20 articles, 13 studies [5][6][7][8][9][12][13][14][15][16][17]22,23) were performed on orthopantomograms for measuring of the size of the pulp cavity and 7 studies 4,10,11,[18][19][20][21] were performed on periapical radiographs. Although most studies included range of age, only one study 23) provided insufficient data of age.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Comparing different body parts for age estimation, teeth show the least changes after death and can also be checked in living individuals. 3 Age can be assessed in children by studying the different phases of root completion according to the Demirjian method.…”
mentioning
confidence: 99%